2006
DOI: 10.1158/0008-5472.can-06-0557
|View full text |Cite
|
Sign up to set email alerts
|

E6AP Mediates Regulated Proteasomal Degradation of the Nuclear Receptor Coactivator Amplified in Breast Cancer 1 in Immortalized Cells

Abstract: The steroid receptor coactivator oncogene, amplified in breast cancer 1 (AIB1; also known as ACTR/RAC-3/TRAM-1/SRC-3/p/ CIP), is amplified and overexpressed in a variety of epithelial tumors. AIB1 has been reported to have roles in both steroiddependent and steroid-independent transcription during tumor progression. In this report, we describe that the cellular levels of AIB1 are controlled through regulated proteasomal degradation. We found that serum withdrawal or growth in high cell density caused rapid deg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
60
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 63 publications
(61 citation statements)
references
References 50 publications
1
60
0
Order By: Relevance
“…We have previously shown that AIB1 protein levels are greatly reduced in response to growth of cells at high confluence and the removal of growth factors (62). Interestingly, we found that the AIB1-⌬4 isoform is not regulated in the same fashion as AIB1 protein (supplemental Fig.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…We have previously shown that AIB1 protein levels are greatly reduced in response to growth of cells at high confluence and the removal of growth factors (62). Interestingly, we found that the AIB1-⌬4 isoform is not regulated in the same fashion as AIB1 protein (supplemental Fig.…”
Section: Discussionmentioning
confidence: 63%
“…This is probably due to loss of a site of regulation in the N-terminal 223 amino acids. The proteasomal regulation of AIB1 has been well characterized (57,62,63). Interestingly, regulation of a phospho-degron at Ser 102 by protein phosphatase 1 (PP1) was shown to be important for regulating the activity of AIB1.…”
Section: Discussionmentioning
confidence: 99%
“…4D), thus likely reduces ubiquitin-mediated degradation, hence increases protein abundance. Because there are several ubiquitin-E3 ligases that can lead to degradation of NCOA3, including Fbw7␣, E6AP, and CHIP (47,(51)(52), it is not clear at the moment which one of them, or all of them, is sensitive to SUMO-induced resistance. It is also possible that sumoylation alters NCOA3 sensitivity toward ubiquitin-independent REG␥-mediated degradation of NCOA3 (49).…”
Section: Discussionmentioning
confidence: 99%
“…1B). It is known that NCOA3 protein level is subject to regulation through both ubiquitin-dependent and ubiquitin-independent mechanisms by REG␥ and aPKC as well as several ubiquitin E3 ligases, such as Fbw7␣, E6AP, and CHIP (47)(48)(49)(50)(51)(52). It is possible that SYT is less potent than SYT-SSX1 in increasing sumoylation of NCOA3, thus at certain cellular level of PIASy activity, SYT is no longer able to protect NCOA3 protein through sumoylation.…”
Section: Ssx1 (mentioning
confidence: 99%
“…1F). However, the screen did not identify with high confidence any of the other E3 ligases (CUL-1-skp1-Fbw7α and E6AP) previously reported to regulate SRC-3 degradation (4,8) (Fig. 1F).…”
mentioning
confidence: 87%